PERAN WORLD HEALTH ORGANIZATION (WHO) MENGATASI FEMALE GENITAL MUTILATION (FGM) DI MESIR TAHUN 2008-2012 - Cut Riani Oetari R; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This papper describe the role of world health organization in preventing Female genital mutilation. FGM in egypt isThe theory that has been employed in this papper was the role based on walker in which enables to explain a symbolic value not only for individual but also groups. Unit analisis that has been used international organization with human security consept was targetet to analysis traditional security.The result of this papper has proved that WHO released a resolution of fight FGM to support egypt goverment to improve Egypt legislation especially in war againts of human rightKeyword : FGM, Egypt, WHO, Resolution, internasional Organization